Vozes que latem: práticas de consumo na relação humano-pet - Silva, Helton Rodolfo Mendes Leal da (2025)
Purpose: This dissertation aims to critically analyze the impact of communication mediation technologies between pet owners and companion animals on social practices of care and consumption. The research examines how such technologies reconfigure human–animal relations, influence the redistribution of agency, and reproduce or challenge the subalternity of nonhumans within consumer practices. Method/Approach: The study adopts a qualitative, interpretivist approach, designed as a single, exploratory case study focused on investigating how mediation technologies transform communication and consumption in the relationship between humans and pets. Data collection involved the analysis of user reviews of pet communication mediation apps, triangulated with in-depth interviews conducted with pet owners and professionals from the pet ecosystem. Data analysis was carried out through hybrid coding—combining predefined theoretical categories and emergent codes—in order to construct analytical categories that reveal the texture of practices. This strategy enabled an understanding of how humans and animals co-produce meanings and consumption decisions mediated by technological interfaces. Findings: The findings of this study indicate that vocal translation applications between humans and pets, although limited in terms of technical accuracy, are configured as sociomaterial actors central to the tutor–animal relationship. More than mere entertainment devices, they highlight the protagonism of pets in consumption decisions, positioning them as agents who reorient everyday practices of care, relational performance, and symbolic expression. In this process, new materialities and meanings emerge that compose the texture of practices (Gherardi, 2009; 2019), confirming Warde’s (2005) proposition that consumption is always social and situated, traversed by affects, disputes, and improvisations. By evidencing how animal agency is mediated and how multispecies practices are organized around technology, this study contributes to expanding practice theory by incorporating the interspecies and technological mediation dimension into the analysis of pet keeping practices. Originality/Value: The study provides a novel contribution by integrating posthumanist perspectives, practice theory, and the sociology of consumption to critically analyze technological mediations in interspecies communication. It proposes a theoretical– methodological model to account for nonhuman agency in sociotechnical ecologies, with implications for marketing, animal ethics, and the design of technologies oriented toward care. Implications for research, practice, and society: Academically, the dissertation expands the debate on animal agency and technological mediation, suggesting new methodological avenues for multispecies research. In practice, it offers insights for the ethical development of products and services in the pet sector, attentive to relational and affective dynamics between humans and animals. At the societal level, it advances a critical reflection on the limits of humanization and the risks of animal instrumentalization, urging companies, developers, and consumers to rethink their relations with nonhumans in more inclusive and sensitive ways. This research aligns with SDG 12 – Responsible Consumption and Production (UN, 2015) by examining how technologies that mediate communication between humans and companion animals influence everyday practices, consumption decisions, and ethical perceptions of animal welfare. By understanding how pet owners incorporate devices and applications into the care and listening of their pets, the study contributes to reflections on more conscious, empathetic, and sustainable forms of consumption.